PENGARUH IPK DAN MOTIVASI DALAM MEMPREDIKSI KETEPATAN WAKTU KELULUSAN MAHASISWA DENGAN MENGGUNAKAN SISTEM PAKAR BERBASIS ADAPTIVE NEURO FUZZY - Yohannes Yahya Welim; T.W Wisjhnuadji (Bit (Fakultas Teknologi Informasi Universitas Budi Luhur), 2013)
In study discussed the relationship between GPA and influence student motivation toward their graduation timeliness in Strata I program a maximum of 8 semesters. The methodology used is based Expert System Modeling Adaptive Neuro Fuzzy. Simulations were performed with MATLAB software Ver.8 produce a model of expert system that is able to predict the exact time graduation rate for students is based on two input parameters, namely GPA (Grade Point Average Index) and Student Motivation Student in following the educational process. The result is that students with GPA above 3.00 and have a high motivation to lecture graduate generally in no more than 8 semesters.Keywords: ANFIS, MATLAB, RMSE, GPA, Motivation, Adaptive Neuro Fuzzy